Effect of Litsea cubeba and Cinnamon Essential Oil Nanoemulsion Coatings on the Preservation of Plant-Based Meat Analogs - Yiqun Zhu; Mengqing Gu; Yuhan Su; Zhe Li; Tiemin Xie; Yifan Zhang; Guohua Qiao; Fei Lu; Chunyang Han (Foods)
Plant-based meat analogs (PBMAs) are promising sustainable food sources. However, their high moisture and protein contents make them prone to microbial deterioration, limiting their shelf life and sensory appeal. This study explored enhancing PBMAs’ shelf life using nanoemulsions of Litsea cubeba and cinnamon essential oils, emulsified with chitosan and Tween 80. The composite nanoemulsion, produced through high-pressure homogenization, exhibited a droplet size of 4.99 ± 0.03 nm, a polydispersity index (PDI) of 0.221 ± 0.008, and a zeta potential of 95.13 ± 2.67 mV, indicating remarkable stability (p < 0.05). Applied to PBMAs stored at 4 °C, it significantly improved color and pH balance and reduced thiobarbituric acid reactive substances and cooking loss. Most notably, it inhibited the growth of Escherichia coli and Staphylococcus aureus, curbing spoilage and protein oxidation, thereby extending the products’ shelf life and preserving sensory quality. As shown above, the encapsulation of LCEO/CEO in nanoemulsions effectively inhibits spoilage and deterioration in PBMAs, improving flavor and quality more than direct addition. Future studies should explore using various essential oils and emulsifiers, as well as alternative encapsulation techniques like microcapsules and nanoparticles, to further prevent PBMA deterioration.